2007
DOI: 10.1302/0301-620x.89b2.18519
|View full text |Cite
|
Sign up to set email alerts
|

Blood and urine metal ion levels in young and active patients after Birmingham hip resurfacing arthroplasty

Abstract: This is a longitudinal study of the daily urinary output and the concentrations in whole blood of cobalt and chromium in patients with metal-on-metal resurfacings over a period of four years. Twelve-hour urine collections and whole blood specimens were collected before and periodically after a Birmingham hip resurfacing in 26 patients. All ion analyses were carried out using a high-resolution inductively-coupled plasma mass spectrometer. Clinical and radiological assessment, hip function scoring and activity l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 28 publications
0
83
0
Order By: Relevance
“…Daniel et al [5,14] reported a significant increase of Co and Cr in the blood at one year follow-up to metal-on-metal hip resurfacing, with a decreasing trend at four and six years after surgery. Within metal-on-metal hip resurfacing, higher levels of metal ions are observed in patients with smaller device diameter [1,11,12,14,22,23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Daniel et al [5,14] reported a significant increase of Co and Cr in the blood at one year follow-up to metal-on-metal hip resurfacing, with a decreasing trend at four and six years after surgery. Within metal-on-metal hip resurfacing, higher levels of metal ions are observed in patients with smaller device diameter [1,11,12,14,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Case et al [3] discovered the possibility of DNA damage due to Co and Cr following metal-on-polyethylene hip arthroplasty. Furthermore, there are concerns about the hazard of delayed-type hypersensitivity reactions, nephrotoxicity and teratogenicity [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical disadvantages of hip resurfacing include the risk of femoral neck fracture [6,63], component malpositioning secondary to increased surgical complexity [20,24], femoral component loosening [5,8,18], decreased head-neck offset causing impingement [22,24], and metal ion production [36,59]. In the 1970s, hip resurfacing with metal femoral components and cemented polyethylene acetabular components was popular, but early failures (30% to 56%) [50,85] within 5 years resulting from osteolysis and component loosening caused them to fall out of favor [7,50,85].…”
Section: Introductionmentioning
confidence: 99%